Answer:
Second Option
f(x) − 2
Step-by-step explanation:
The function [tex]y=3 (2) ^ x[/tex] passes through point (0, 3) because:
[tex]f (0) = 3 (2) ^ 0 = 3 (1) = 3[/tex]
Then, if the transformed function passes through the point (0, 1) then this means that the graph of [tex]y = 3 (2) ^ x[/tex] was moved vertically 2 units down.
The transformation that displaces the graphically of a function k units downwards is:
[tex]y = f(x) + k[/tex]
Where k is a negative number. In this case [tex]k = -2[/tex]
Then the transformation is:
[tex]y = f(x) -2[/tex]
and the transformed function is:
[tex]y = 3(2) ^ x -2[/tex]